A pilot economic evaluation of a feasibility trial for SUpporting wellbeing through PEeR-Befriending (SUPERB) for post-stroke aphasia. (May 2022) - Flood, Chris; Behn, Nicholas; Marshall, Jane; Simpson, Alan; Northcott, Sarah; Thomas, Shirley; Goldsmith, Kimberley; McVicker, Sally; Jofre-Bonet, Mireia; Hilari, Katerina
Objectives: To explore the feasibility of a full economic evaluation of usual care plus peer-befriending versus usual care control, and potential cost-effectiveness of peer-befriending for people with aphasia. To report initial costs, ease of instruments' completion and overall data completeness. Design: Pilot economic evaluation within a feasibility randomised controlled trial Setting: Community, England Participants: People with post-stroke aphasia and low levels of psychological distress Intervention: All participants received usual care; intervention participants received six peer-befriending visits between randomisation and four months Main measures: Costs were collected on the stroke-adapted Client Service Receipt Inventory (CSRI) for health, social care and personal out-of-pocket expenditure arising from care for participants and carers at 4- and 10-months post-randomisation. Health gains and costs were reported using the General Health Questionnaire-12 and the EQ-5D-5L. Mean (CI) differences for costs and health gains were reported and uncertainty represented using non-parametric bootstrapping and cost-effectiveness acceptability curves. Results: 56 participants were randomised. Mean age was 70.1 (SD 13.4). Most ( n  = 37, 66%) had mild and many ( n  = 14; 25%) severe aphasia. There was ≥94% completion of CSRI questions. Peer-befriending was higher in intervention arm ( p  < 0.01) but there were no significant differences in total costs between trial arms. Peer-befriending visits costed on average £57.24 (including training and supervision costs). The probability of peer-befriending being cost-effective ranged 39% to 66%. Conclusions: Economic data can be collected from participants with post-stroke aphasia, indicating a full economic evaluation within a definitive trial is feasible. A larger study is needed to demonstrate further cost-effectiveness of peer-befriending.